RANCANG BANGUN SISTEM HIDROPONIK NFT BERBASIS ARDUINO DENGAN SUMBER TEGANGAN PLTS - Stefany Margareta Martono; Serli Liling Allo; Sonny Rumalutur (LPPM Poltek ST Paul, 2023)
Hydroponics is a technique of cultivating plants with water that has been added with AB Mix nutrients. The hydroponic system used in this research is NFT. This system uses shallow water and is circulated continuously for 24 hours using a pump so that plants can get sufficient water, nutrients and oxygen. The electricity supply from PLN is not always available and the hydroponic system is not always made in places where PLN electricity is available, therefore in this research the voltage source comes from PLTS. In this research, a 50 Wp polycrystalline solar panel and a 70 Ah battery were used. To produce plants with optimal development, proper nutrition and pH are needed. Therefore, an Arduino-based pH and nutrition monitoring system is used. The results of pH and nutrient readings are displayed on the LCD screen. If the pH and nutrient level readings are outside the predetermined level, the buzzer will sound. To adjust the pH and PPM of hydroponic water to suit the needs of plants, you need to add a pH regulator and AB Mix to the hydroponic water. From the experiment, for every 5 mL of pH down added to 20 L of hydroponic water, the pH will decrease by 0.27, while for every 5 mL of solution A and 5 mL of solution B, there will be an increase in PPM of 50.89.